Expenditure Control : Key Features, Stages, and Actors - Pattanayak, Sailendra (Technical Notes and Manuals; Technical Notes and Manuals, 2016)
This paper defines and explains key stages of the government expenditure chain and describes the controls applied at each stage, including their objectives and key features as well as centralized vs. decentralized approaches in application of those controls. The paper also examines the influence of different administrative traditions on types of expenditure controls, including the authority and responsibility of various institutional actors. Finally, it discusses typical weaknesses/problems associated with different traditions of expenditure control and suggests specific measures for strengthening the control framework. While providing examples of expenditure control practices from more than 32 countries, the paper points out that more than two-thirds of the 85 low and middle income countries covered by the publicly available Public Expenditure and Financial Accountability (PEFA) assessments have weak systems of expenditure control that are also associated with higher levels of expenditure arrears and a lack of budget credibility. This paper will help public financial management practitioners to evaluate budget execution systems and identify priorities for strengthening expenditure controls. It will also usefully guide technical assistance work related to modernization of government budget execution and expenditure control systems, including the design and implementation of IT-based financial management information systems.